Предмет: Алгебра,
автор: sergeysp2008sp48
Розв’язати рівняння
1)2х(3х – 4) – 3х(2х + 5) =7;
2)х(6 - х) – 7(6- х) = 0
Ответы
Автор ответа:
3
Ответ:
1)2х(3х – 4) – 3х(2х + 5) =7
6х²-8х-6х²-15х=7
-23х=7
х=7/(-23)
х=-0.3
2)х(6 - х) – 7(6- х) = 0
6х-х²-42+х=0
х²-7х+42=0
D=b^2−4ac=−119
корней нет, т.к. D<0
Объяснение:
Похожие вопросы
Предмет: Английский язык,
автор: Арина34242
Предмет: Английский язык,
автор: танюшка195
Предмет: Русский язык,
автор: спроси4
Предмет: Математика,
автор: farizafaxriddinovna
Предмет: Математика,
автор: alesha71